2001
DOI: 10.1007/s004170100254
|View full text |Cite
|
Sign up to set email alerts
|

Pars-plana vitrectomy in cystoid macular edema associated with intermediate uveitis

Abstract: Pars-plana vitrectomy led to regression of CME in 59% of cases and to subsequent improvement of VA in 50% of eyes with intermediate uveitis. PPV should be considered soon after medical therapy has been shown to be ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 32 publications
1
17
0
6
Order By: Relevance
“…This finding is in line with previously published reports in adults. 4,6 With the present regression model, 44% (coefficient of determination, R 2 ¼ 0.44) of the variation of the final logMAR acuity is thereby explained. The remaining part of the variation must be explained by other unknown individual patient factors.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This finding is in line with previously published reports in adults. 4,6 With the present regression model, 44% (coefficient of determination, R 2 ¼ 0.44) of the variation of the final logMAR acuity is thereby explained. The remaining part of the variation must be explained by other unknown individual patient factors.…”
Section: Discussionmentioning
confidence: 82%
“…17,18 Several studies with adult patients showed a greater variation of the CME regression rate (32.4-82.4%). [4][5][6]9,10,12 The abovementioned meta-analysis showed a regression rate of 47.4% after PPV. 23 This fact may suggest a better inflammatory CME resolution rate in paediatric patients than in adults after PPV.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Median CRT (95% CI) was 591.8 microns (234.5; 949) in non-PPV eyes and 557.3 microns (264.6; 850) in PPV eyes at baseline; its maximum decrease was at first month, 340.6 microns (18.5; 662.7) and 327.4 microns (44.8; 610), respectively, ( Table 2) and this improvement was maintained in both groups during 5 [5,6]; N = 19 (5-7) 5 [5,6]; N = 10 (5-7) 5 [5,6]; N = 9 (5-7) 0. Eye the entire follow-up.…”
Section: Demographics and Uveitis Diagnosismentioning
confidence: 87%
“…2,3 In addition, some studies advocate performing pars plana vitrectomy in patients with uveitic ME as a therapeutic procedure if more conservative measures failed. [4][5][6] A consequence of pars plana vitrectomy is that some intravitreal pharmacological treatments may have a reduced half-life in vitrectomized (PPV) eyes, possibly as a result of increased clearance. 6 This decreased duration of effect may lead to a need for more frequent injections.…”
Section: Introductionmentioning
confidence: 99%